2003
DOI: 10.1038/sj.npp.1300194
|View full text |Cite
|
Sign up to set email alerts
|

Null Mutation of the Arginine-Vasopressin Gene in Rats Slows Attentional Engagement and Facilitates Response Accuracy in a Lateralized Reaction Time Task

Abstract: The neurophysin vasopressin is thought to play an important role in emotional behavior and aspects of cognition in the rat, and the pathophysiology of this system has been implicated in two neurodevelopmental disorders, namely autism and schizophrenia. Genetic deficiency of vasopressin in rats, resulting from a null mutation of the vasopressin gene, causes alterations of brain development with resulting behavioral and neurochemical phenotypes in adulthood. We previously demonstrated that partial vasopressin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Clearly, more research is needed to assess how sex b r a i n r e s e a r c h 1 5 3 7 ( 2 0 1 3 ) 1 7 4 -1 7 9 differences may interact with vasopressin to account for potential behavioral or cognitive effects. The studies conducted by Jentsch et al (2003) and Jentsch (2003), which used a lateralized reaction time task (see the Introduction section) in male rats, provide the closest comparisons possible with the present study's findings. In the study by Jentsch (2003), HZ rats failed to exhibit differences in choice accuracy at 30, 5, and 2.5 s durations but displayed improved choice accuracy at a 1 s duration.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Clearly, more research is needed to assess how sex b r a i n r e s e a r c h 1 5 3 7 ( 2 0 1 3 ) 1 7 4 -1 7 9 differences may interact with vasopressin to account for potential behavioral or cognitive effects. The studies conducted by Jentsch et al (2003) and Jentsch (2003), which used a lateralized reaction time task (see the Introduction section) in male rats, provide the closest comparisons possible with the present study's findings. In the study by Jentsch (2003), HZ rats failed to exhibit differences in choice accuracy at 30, 5, and 2.5 s durations but displayed improved choice accuracy at a 1 s duration.…”
Section: Discussionsupporting
confidence: 52%
“…In the study by Jentsch (2003), HZ rats failed to exhibit differences in choice accuracy at 30, 5, and 2.5 s durations but displayed improved choice accuracy at a 1 s duration. In another lateralized reaction time study, Jentsch et al (2003) reported that BRAT rats showed improved choice accuracy at a 2.0 s duration but displayed impaired choice accuracy at a 0.2 s duration. Considering these findings together, Jentsch et al (2003) suggested that increases in vasopressinergic tone may diminish attention accuracy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After being trained to make the sustained nose poke, rats began daily testing on the lateralized reaction time task (Brown and Robbins 1989;Carli et al 1985;Jentsch et al 2003); in the first four sessions, a target stimulus of fixed duration was presented for all trials in a session (which terminated after 60 min or 128 trials, whichever came first). The task began with the illumination of the house light and the rats retrieving a single pellet from the magazine.…”
Section: Acquisition Of the Lateralized Reaction Time Taskmentioning
confidence: 99%
“…In this task, rats engage in a variable-duration fixation response while waiting for the delivery of a visual target in the left or right visual fields (Brown and Robbins 1989;Carli et al 1985;Jentsch et al 2003). During this fixation response, rats must divide and orient their attention, monitoring both locations for the stimulus delivery; because the temporal onset and duration and spatial localization of the target are unknown to the rats, the subjects will "miss" the target if they attend to only one location and/or fail to sustain their attention.…”
Section: Introductionmentioning
confidence: 99%